Secondary Subcutaneous Rhizopus Infection in a Posttransplant Recipient with Calcific Uremic Arteriolopathy - Urmila Anandh; Rakesh Kumar; Vishnu Rao (Case Reports in Infectious Diseases)
Calcific uremic arteriolopathy is a rare condition affecting chronic kidney disease (CKD) patients on long-term dialysis. The clinical manifestations include subcutaneous skin necrosis and ulcers secondary to calcification of the subcutaneous blood vessels. The necrotic tissue often becomes a nidus of infection. The prognosis is often poor. We present a case of a renal allograft recipient who developed a subcutaneous necrotic lesion which was subsequently infected by Rhizopus spp. The patient underwent surgical debridement and antifungal therapy. The infection resolved completely. Our case represents agrave underlying condition predisposing a rare and serious posttransplant infection. The outcome was favourable because of early identification and treatment of the infection.